The Use of Yoga in the Treatment of PCOS - Agnieszka Przesor Przezor; Natalia Medźwiedzka (Quality in Sport)
Polycystic ovary syndrome (PCOS) is a complex and common endocrine disorder, and  affects women of reproductive age. Symptoms include multiple ovarian cysts, hyperandrogenism (high levels of male hormones), and irregular menstrual cycles. PCOS is associated with a variety of health problems, including insulin resistance, obesity, hirsutism (excessive hair growth), and fertility problems. Lifestyle interventions and weight loss, if appropriate, remain the first-line treatment for women with PCOS. Regular physical activity is recommended for women with PCOS to maintain a healthy weight and cardiovascular fitness. Yoga is a system of exercises, called asanas, that originates from ancient India. Asana means “comfortable posture,” so any yoga posture is considered optimal for human well-being and balance. There are also more complicated asanas, especially for beginners, that can feel like they are taking away from one’s balance. In addition to asanas, breathing techniques known as pranayama are also very important in yoga. Practicing yoga is an excellent tool in improving the functioning of our entire body, both on the level of psyche and physis, which is why it is especially valuable for patients with PCOS.